Effects of thidiazuron and N6-benzylaminopurine on endogenous hormone levels during regeneration of Brassica campestris ssp. Rapifera - MA Guang; GUO Ji-ping (浙江大学学报. 农业与生命科学版)
To investigate the reason that thidiazuron (TDZ) is more effective than N6-benzylaminopurine (6-BA) in regeneration of Brassica campestris L. ssp. rapifera (Matzg.) Sinsk (syn. B. rapa ssp. rapifera), shoot regeneration was achieved from cotyledonary petiole of in vitro cultures using Murashige and Skoog (MS) medium supplemented with 1-naphthalene-acetic acid (NAA) and TDZ or 6-BA. The regeneration results suggested that the optimal combination was TDZ 4.0 mg·L-1 + NAA 1.0 mg·L-1 or 6-BA 5.0 mg·L-1 + NAA 1.0 mg·L-1, respectively, and the shoot frequency was 80.4% and 30.2%, respectively. The different effects of the two combinations on the endogenous indole-3-acetic acid (IAA), zeatin (Z), gibberellic acids (GAs) and abscisic acid (ABA) contents in cotyledonary petiole explants were studied. Higher endogenous IAA and Z levels induced by TDZ 4.0 mg·L-1 + NAA 1.0 mg·L-1 than 6-BA 5.0 mg·L-1 + NAA 1.0 mg·L-1 were observed. The endogenous GAs and ABA contents induced by the two combinations were similar, respectively. The ratio of IAA/ABA and IAA/Z both shifted towards IAA. The ratio of IAA/ABA induced by TDZ was higher than 6-BA, and no visible different effect on IAA/Z between TDZ and 6-BA. The results revealed that higher levels of IAA, and ratio of IAA/ABA were two critical factors, but ABA and GAs had no effect on more effective regeneration induced by TDZ than 6-BA. The roles of Z and IAA/Z were uncertain and should be investigated in further works.